2009
DOI: 10.3233/jad-2009-1189
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Neurogenesis and Synaptogenesis by Bilobalide and Quercetin via Common Final Pathway in Hippocampal Neurons

Abstract: Loss of synapses has been correlated with dementia in Alzheimer's disease (AD) as an early event during the disease progression. Hence, synaptogenesis and neurogenesis in adulthood could serve as a therapeutic target for the prevention and treatment of AD. Recently, we have demonstrated enhanced hippocampal neurogenesis by oral administration of Ginkgo biloba extract (EGb 761) to a mouse model of AD. This study aims to identify the constituents that contribute to EGb 761-induced neurogenesis. Among the constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
88
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 63 publications
8
88
0
3
Order By: Relevance
“…Here, the addition of C1q to fA␤-injured neurons resulted in increased phosphorylation and nuclear translocation of CREB, similar to what was observed in nutrient-stressed neurons (10) and in monocytes (46). CREB is a transcription factor vital for long term memory and synaptic plasticity (34), neurogenesis (47)(48)(49), and induction of neurotrophic factors in the CNS (35). In addition, pCREB is a central transcription factor in brain-derived neurotrophic factor signaling (50) and also induces brain-derived neurotrophic factor upon activation (51).…”
Section: Discussionsupporting
confidence: 77%
“…Here, the addition of C1q to fA␤-injured neurons resulted in increased phosphorylation and nuclear translocation of CREB, similar to what was observed in nutrient-stressed neurons (10) and in monocytes (46). CREB is a transcription factor vital for long term memory and synaptic plasticity (34), neurogenesis (47)(48)(49), and induction of neurotrophic factors in the CNS (35). In addition, pCREB is a central transcription factor in brain-derived neurotrophic factor signaling (50) and also induces brain-derived neurotrophic factor upon activation (51).…”
Section: Discussionsupporting
confidence: 77%
“…The increase of Ki67-immunoreactive cells in the DG in this present study is supported by an previous in vitro study, in which bilobalide treatment could induce a significant increase of 5-bromo-2-deoxyguanosine (BrdU) incorporation with a dose-dependent manner in the hippocampal progenitor cells derived from embryonic day 18 in rats [34]. It was reported that 100 mg/kg Gb treatment for 1 month sig- nificantly enhanced cell proliferation in the DG of both adult (6 months) and aged (22 months) Alzheimer mice compared with their untreated counterparts [30].…”
Section: Discussionsupporting
confidence: 76%
“…Repeated treatments with Gb to aged rats elicit robust hippocampal long-term potentiation [36,38]. In addition, bilobalide treatment shows dendritic arborations and welldeveloped dendritic branches in the hippocampal progenitor cells derived from embryonic day 18 in rats [34]. In conclusion, repeated administration of Gb increases cell proliferation and neuroblast differentiation in the hippocampal DG and consumption of Gb may be helpful to increase endogenous neurogenesis in adults.…”
Section: Discussionmentioning
confidence: 92%
“…In vitro and in vivo studies have shown that neuroprotective effects of quercetin are exerted by different molecular mechanisms (19). Our study, in converge with these works, suggested a new possible mechanism for neuroprotection by quercetin.…”
Section: Discussionsupporting
confidence: 71%